Keeping it real: amaXhosa iimbongi making mimesis do its thing in the hip-hop and rap music of the Eastern Cape - Watkins, Lee (International Library of African Music, 2010)
Hip-hop and rap music are present in many cities in the Eastern Cape but this article is restricted to an analysis of the rap music and hip-hop scene in Port Elizabeth and Grahamstown.3 Although the intention of this article is musicological, it is necessary to look at rap music in its contexts, that is, the hip-hop movement locally and globally, and as but one aspect in relation to the other performance and ideological aspects of the hip-hop movement.4 For this reason I attempt to integrate the discursive attributes of the movement into a narrative where the aesthetics of hip-hop performance in the Eastern Cape and South Africa, and by extension, other parts of the globe, is the main concern.
Keywords: African Music